Are there de jure objections to Mādhvic belief?. Issue 4 (December 2022) - Gupta, Akshay
Abstract: Recently, Erik Baldwin and Tyler McNabb have brought Madhva's epistemological framework into active dialogue with Alvin Plantinga's religious epistemology and have argued that individuals within Madhva's tradition cannot make full use of Plantinga's epistemology, according to which, Christian belief resists de jure objections and can also have warrant. While I do not contest this specific claim, I demonstrate that an analysis of Madhva's epistemological framework reveals that this framework has its own resources through which it can resist de jure objections. I address various objections to the rationality of Mādhvic belief and conclude that there are no de jure objections to Mādhvic belief that are independent of de facto objections.